Implementation Of Media Relations Strategy To Increase Company Publicity - Yella Meisha INDIKA; Ade Dermawan NAWAWI; Putri Andari W.A. (International Journal of Environmental, Sustainability, and Social Science, 2022)
Companies require the media in their efforts to develop communication with the public. There are two sides to be addressed through media relations: first, build positive relationships and connect with the mass media. Second, make the mass media partners so organizations can communicate with the public. This study aims to determine the effectiveness of the company's media relations strategy. Because creating positive or negative publicity depends on how relations with the media can be built, this type of research uses qualitative research with a case study approach. The respondents of this research are the management and employees of companies located in Jakarta. At the same time, the data collection technique used interviews, and documentation was used as secondary data derived from books, studies or previous research relevant to the objectives of the related research. The data analysis technique uses reduction, data presentation, and verification. The results of this study show that media relations strategies such as press releases, press conferences, press visits, and media meetings boost a company's image in the public consciousness and influence society's image formation. Media relations are implemented to build good media relations and obtain positive publicity. Maintaining solid media contacts also helps. So every company needs to establish good relations with the media because the company's publicity depends on how the relationship is formed. That is why, media relations are very strategic for companies to carry out their activities to increase their publicity.